Changes in novel cardiac extracellular matrix biomarkers in STEMI: associations with adverse outcomes. (3rd October 2022) - Andrup, S; Andersen, G Ø; Hoffmann, P; Eritsland, J; Seljeflot, I; Halvorsen, S; Vistnes, M
Abstract: Background: Ischemia-reperfusion (IR)-injury contributes to adverse outcomes following myocardial infarction undergoing reperfusion. Exaggerated remodelling of the extracellular matrix (ECM) is likely to be involved in IR-injury, potentially releasing ECM components to the systemic circulation. To improve prognostication and future therapeutic options in patients with myocardial infarction, more knowledge is warranted about ECM components associated with IR-injury. Purpose: To investigate whether ECM components quantified in serum samples associate with myocardial injury and function, and clinical outcomes in patients with ST-elevation myocardial infarction (STEMI). Methods: We selected biomarkers previously suggested to be involved in ECM changes in the heart, i.e. growth differentiation factor 15 (GDF-15), periostin, osteopontin, syndecan-1, syndecan-4, and bone morphogenetic protein 7. The concentrations of the biomarkers were measured in serum samples from patients with STEMI (n=239) enrolled in the POSTEMI trial, at day 1 and month 4 after hospital admission. Infarct size, microvascular obstruction (MVO), left ventricular remodelling, and left ventricular ejection fraction (LVEF) were determined by cardiac magnetic resonance imaging. Major adverse cardiovascular events (MACE) and all-cause mortality were recorded after 12 months and with a median of 70 months, respectively. Results: Serum levels of GDF-15, osteopontin, syndecan-1 and syndecan-4 declined, whereas periostin increased, from day 1 to month 4. Higher levels of syndecan-1 were associated with the presence of MVO (n=116) (day 1 OR 1.39 (1.06–1.82); month 4 OR 1.53 (1.08–2.17)), while higher GDF-15 and syndecan-1 were associated with the development of large infarct size (>75th percentile, n=57) and reduced cardiac function defined as LVEF <50% (n=64) at month 4. Higher levels of GDF-15 at month 4 and periostin at both time points were associated with increased risk of both MACE (n=16) (GDF-15: HR 1.42 (1.04–1.94); periostin day 1: HR 1.88 (1.09–3.25); periostin month 4: HR 1.64 (1.03–2.62)) and all-cause mortality (n=20) (GDF-15: HR 1.59 (1.28–1.97); periostin day 1: HR 1.85 (1.16–2.95); periostin month 4: HR 2.02 (1.35–3.02)) (Figure 1). On the contrary, elevated levels of syndecan-4 at month 4 were associated with lower risk of adverse outcomes, including all-cause mortality (HR 0.48 (0.28–0.84)) (Figure 1) and less IR-injury as assessed by a higher myocardial salvage index. Conclusion: Elevated serum levels of GDF-15, periostin, and syndecan-1 were associated with a higher risk of adverse outcomes or detrimental remodelling in patients with STEMI. Increased levels of syndecan-4 measured 4 months after STEMI were associated with a reduced risk of all-cause mortality. Our results suggest the potential use of these biomarkers as prognostic tools and may suggest a role for these ECM components in IR injury. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): South-Eastern Norway Regional Health AuthorityNorwegian Health Association